EMG-Modell of the backstroke start technique - Hohmann, A.; Fehr, U.; Kirsten, U.; Krüger, T. (Biomechanics and Medicine in Swimming X, 2006)
This study researched in more depth a 6-phase model that describes die time pattern and die activity level of die muscles while executing the backstroke Start. Five male backstroke Sprinters of die German national swim team performed four backstroke Starts over a distance of 7.5 m. EMG-data were recorded by a water protected 8-channel EMG from eight arm, shoulder, trunk and leg muscles. To compare die quality of muscular activity patterns, die IDANCO-system served as a quantitative method. The EMG recordings in die 5 swimmers indicated a medium repetition consistency and reproducibility of die identified patterns of muscle activity. In die initial hang phase, and the final glide phase die EMG recordings of die first dolphin kick demonstrated an identical and analogue movement behaviour. During the flight phase, and especially during die water entry the number of different muscle activation patterns grew signifkantly.